2011
DOI: 10.1103/physrevlett.107.053401
|View full text |Cite
|
Sign up to set email alerts
|

Three-Electron Interatomic Coulombic Decay from the Inner-Valence Double-Vacancy States in NeAr

Abstract: We have unambiguously identified interatomic Coulombic decay in NeAr from the inner-valence double-vacancy state Ne-Ar(2+)(3s(-2)) to outer-valence triple-vacancy states Ne(+)(2p(-1))-Ar(2+)(3p(-2)) by momentum-resolved electron-ion multicoincidence. This is the first observation of interatomic Coulombic decay where three electrons (3e) participate. The results suggest that this 3e interatomic Coulombic decay is significantly faster than other competing processes like fluorescence decay and charge transfer via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…An analogous unusual process where a double vacancy is filled by two electrons and a single photon is emitted was already known [4], but no three-electron Auger process had been demonstrated at that time. More recently a three-electron Auger process was suggested as a possible explanation of an observed feature in a beam-foil excited C 3+ ion [5], and a related process was more clearly predicted and observed in a rare-gas dimer [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…An analogous unusual process where a double vacancy is filled by two electrons and a single photon is emitted was already known [4], but no three-electron Auger process had been demonstrated at that time. More recently a three-electron Auger process was suggested as a possible explanation of an observed feature in a beam-foil excited C 3+ ion [5], and a related process was more clearly predicted and observed in a rare-gas dimer [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…It is now well known that ICD appears everywhere and transfers the energy and the charge from the excited species to the environment surrounding it. Also, it is known that there are many variants of ICD, such as ICD from satellite states [4][5][6][7], ICD after Auger decay [8][9][10][11][12][13][14], resonant ICD [15][16][17] where inner-valence excited states decay via ICD-like spectator decay, and three-electron ICD [18,19] where two inner-valence holes in a species are filled by ICD in which three electrons are involved. Another exotic variant, called electron-transfer-mediated decay (ETMD), was also predicted [20] and observed [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…ICD takes place from the Auger final states that have an inner-valence hole [8]. The branching ratio to these states is, however, only of the order of 10% [9,13,19]. In turn, a well-established method of site-specific excitation is resonant core excitation; using the chemical shift, one can select not only a specific kind of atom but also a specific site of the same kind of atom located at different sites.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown since then that ICD is a very general phenomenon occuring in van der Waals bound (see e.g. [2][3][4][5]) and hydrogen bound systems (see e.g. [6][7][8]).…”
Section: Pacs Numbersmentioning
confidence: 99%